57.8k views
3 votes
(3x + 5) (x2 – 10x + 2 ).

2 Answers

2 votes

Answer:

3x^3 + 25x^2 - 44x +10

Explanation:

To answer this use FOIL

First Outer Inner Last

In this problem start by distributing the 3x

3x^3-30x^2+6x

Next distribute the 5 in the second parenthesis

5x^2 - 50x + 10

Lastly, add like terms (terms that have the same variable and powers)

3x^3 - 25x^2 +6x +10

User Ribeiro
by
5.4k points
2 votes

Answer:


3x^(3) -25x^(2) -44x+10

Explanation:

Hello!

To solve this we distribute what in one parenthesis into the other

3x

3x * x^2 = 3x^3

3x * -10x = -30x^2

3x * 2 = 6x

5

5 * x^2 = 5x^2

5 * -10x = -50x

5 * 2 = 10

Now we put like terms together and simplify

3x^3 + 0 = 3x^3

-30x^2 + 5x^2 = 25x^2

6x - 50x = -44x

0 + 10 = 10

Put it all together

3x^3 + 25x^2 - 44x + 10

Hope this helps!

User Narendra Modi
by
4.7k points